THE CHARACTERISTICS OF SALTED EGG IN THE PRESENCE OF LIQUID SMOKE - J M W Wibawanti; M Meihu; A Hintono; Yoyok Budi Pramono (Indonesian Food Technologists, 2013)
Salted egg is one of the most traditional and popular preserved egg products. Therefore, the objectives of this study were to investigate the changes on the characteristics of duck egg salted at different times. Currently, diversification of product salted egg could be used Liquid Smoke (LS). Split Plot in time with a basic design Completely Randomized Design (CRD) was used throughout the research. They were run triplicate.The viscosity of egg white control was significant compared with salted egg of LS treatment (p < 0.05). Moisture content and total solid of egg white control was significant compared to that salted egg with LS treatment (p < 0.05). The viscosity of egg white and moisture contain decreased from an initial value (p < 0.05). Moisture contents and total solid of egg yolk control were no different statistically compared to that salted egg of LS treatment (p > 0.05). Significant of total solid along was increased during salting time (p < 0.05).